PENYUSUNAN BUKU “BERCERITA UNTUK BINA DAMAI: KUMPULAN CERITA RAKYAT DARI BERBAGAI PENJURU DUNIA” - Elyzabeth Bonethe Nasution; Edwin Martua Bangun Tambunan (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
Storytelling is believed to be an effective instrument in passing on knowledge, values, and characters. Not only in Indonesia, but storytelling is also performed by various nations across the earth. Storytelling allows people to enjoy the entertaining process of values or characters construction. People learn without feeling lectured. Peace studies scholars have proven the contribution of story and storytelling in keeping the memory, recovering, and peacebuilding. Having that acknowledged, the Youth & Peace Project under the Department of International Relations initiated the idea of creating a book entitled “Bercerita untuk Bina Damai: Kumpulan Cerita Rakyat dari Berbagai Penjuru Dunia.” It is safe to say that this is a blessing in disguise from Covid-19 pandemic. Our students who should have had their internships on the field then enrolled in one course as alternative. The idea was then integrated to Conflict Resolution class. Students were asked to retell a story that has peace aspect. After a tight screening and reviewing process, this book is published. Its main objective is as peacebuilding reading material that can be read to anyone and anytime or to be used as ice breaking/closing activity during a workshop/community service.